Historical conceptualizations of the legal figure: conscientious objection - Pérez Rocha, Jonatan (2022)
This article deals with the concept of conscience, its philosophical-moral approaches, and its relations with the birth of the legal figure called conscientious objection through a phenomenological historical journey, in conjunction with the history of human rights, bioethics and biolaw. Reviews the international emergence of parallel concepts that saw the birth of the legal figure. It addresses concepts such as belief and ideology or other meanings such as civil disobedience. As part of its methodology, it historically systematizes the concept of conscience and the historical-philosophical bases that support its defense and its disagreements with certain ethical principles when applying the law. It contains notes that illustrate the current state of the issue from the Costa Rican legal reality, to close with some considerations on conscientious objection, linked to rulings given by the Constitutional Chamber of Costa Rica.